2006
DOI: 10.4103/0973-1482.25848
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia today: Electric energy, a new opportunity in cancer treatment

Abstract: Hyperthermia is an ancient, but nowadays rapidly developing treatment method in tumor-therapy. Its new paradigm applied in the electro-hyperthermia (oncothermia), which provides energy by means of electric-field and produces non-equilibrium thermal situation in the tissue. The temperature gradients formed in stationary conditions, destroy the membrane of the malignant cells and selectively eliminate the cancer tissue. The characteristic control parameter is the absorbed energy-dose, which is partly used to mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 49 publications
0
51
0
Order By: Relevance
“…The change of the temperature paradigm was urged on a theoretical basis [36,39], supported by clinical observations as well [12,38]. In the light of the present experimental results, the temperature effect alone misleads the discussions [39].…”
Section: Discussionmentioning
confidence: 56%
“…The change of the temperature paradigm was urged on a theoretical basis [36,39], supported by clinical observations as well [12,38]. In the light of the present experimental results, the temperature effect alone misleads the discussions [39].…”
Section: Discussionmentioning
confidence: 56%
“…Elevated glycolysis in tumor cells, known as the Warburg effect, can increase permittivity and conductivity (Andocs et al 2009b;Blad and Baldetorp 1996;Blad et al 1999;Fiorentini and Szasz 2006;Zou and Guo 2003), which support mEHT to selectively damage tumor cells (Andocs et al 2009a) without affecting normal tissues. The electric field and heat can induce cellular stress signals (Balogh et al 2013) leading to Bax-mediated mitochondrial dysfunction, pore formation, and programmed cell death (Meggyeshazi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Modulated electrohyperthermia (mEHT) is a non-invasive local technique using capacitive coupled 13.56-MHz radiofrequency for targeted destruction of tumor cells (Andocs et al 2009a) based on the elevated conductivity, permittivity, and current density in cancer compared to normal tissue (Andocs et al 2009b;Blad and Baldetorp 1996;Blad et al 1999;Fiorentini and Szasz 2006;Zou and Guo 2003). We have previously revealed that mEHT at <42°C can dominantly induce a caspase-independent programmed cell death in HT29 colorectal cancer xenografts as a result of cell stress synergistically induced by the electric field and heat (Andocs et al 2009a;Meggyeshazi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…So these points are realized, and this procedure is called modulated electrohyperthermia or oncothermia [46] and it is specialized now for andrology. It is a well-designed capacitive coupling on 13.56 MHz free frequency [47].…”
Section: Methodsmentioning
confidence: 99%